System architecture for personalized automatic audio-visual content generation from Web feeds to an iTV platform - Silva, C. (2018)
Fulfilling informational needs of seniors is vital for a successful development of active ageing and independent living initiatives, which contribute for an effective provision of welfare benefits tailored for these citizens. This paper aims to propose a system architecture for automated generation of audio-visual contents adapted from Web feeds of information about Assistance Services of General Interest for Elderly (ASGIE). These pieces of high-value generated content are tailored to the seniors’ requirements, needs and expectations, for further exhibition on an iTV platform. Also, this paper describes the technical choices leading to a prototype implementation developed in the context of +TV4E project, an ongoing research project of an iTV platform to enrich seniors television experience with the integration of informative content. Future work will involve submitting this prototype and the generated contents to field tests at seniors’ home environment.